2005
DOI: 10.1007/s10725-004-6444-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of p-CPA-parthenocarpic setting on the delayed ripening of netted-melon fruits

Abstract: Application of plant growth regulators may induce parthenocarpic fruit setting, avoiding problems due to poor pollination. Their influence on the ripening of netted-melon fruit (Cucumis melo L.), however, is not yet well understood. The ripening behavior of parthenocarpic melon fruit (treated with 50 ppm 4-chlorophenoxy acetic acid (p-CPA) and 350 ppm gibberellic acid (GA 3 ) at anthesis) was compared with that of hand-pollinated fruit. The ethylene production in parthenocarpic fruit peaked up about 10 days be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Phytohormones such as auxin, gibberellin, and cytokinin can, either individually or in combination, induce parthenocarpy, which improves fruit quality and extends shelf life. Gibberellin in combination with 4-chloro-phenoxyacetic acid are commonly used for artificial parthenocarpy in melons during unfavorable climate conditions (Pariasca et al 2005, Shin et al 2007). The present study observed that CPPU treatments performed at different time points significantly increased the fruit setting rate and qualified rate of pollinated oriental melons by 23% to 26.1% and 21.9% to 35.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones such as auxin, gibberellin, and cytokinin can, either individually or in combination, induce parthenocarpy, which improves fruit quality and extends shelf life. Gibberellin in combination with 4-chloro-phenoxyacetic acid are commonly used for artificial parthenocarpy in melons during unfavorable climate conditions (Pariasca et al 2005, Shin et al 2007). The present study observed that CPPU treatments performed at different time points significantly increased the fruit setting rate and qualified rate of pollinated oriental melons by 23% to 26.1% and 21.9% to 35.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%